CONSTRAINING FACTORS ON IMPLEMENTATION DISASTER MANAGEMENT POLICY IN PADANG CITY - Zulfadrim, . (FIA UB, 2013)
Abstract: Constraining Factors On Implementation Disaster Management Policy In Padang City. In creating bigger roles for the people, the new approach shall be community-based and will focus on ways to encourage and invite more active participation from the members of the community to propose ideas in the planning, implementation, and evaluation of the program. Stakeholders at various levels, including the government, will work in a single, coordinated effort. To make the system effective, the development of local response capability has to be addressed with same level of commitment and investment provided to the development of the technological components. Human capacities at all levels need to be developed to increase the institutional response capability at the local level. To build a common understanding of the system and to encourage all actors to accept and play their respective roles, the provision of sufficient funding, adequate capacity development and instructive guidelines is essential. Developing these guidelines is a multi-stakeholder task. Only a joint learning process can lead to a tailor-made warning chain and public outreach strategies that really address the needs of the community at risk. Results and experiences from this learning process need to be systematized and documented. Keywords: disaster managements, preparedness. Abstrak: Faktor-Faktor yang Mempengaruhi Implementasi Kebijakan Manajemen Bencana di Kota Padang. Pemangku kepentingan di berbagai tingkatan, termasuk pemerintah, akan bekerja dalam suatu bentuk koordinasi yang terpadu. Untuk membuat sistem yang lebih efektif, peningkatan kapasitas masyarakat harus bersinergi dengan komitmen dan investasi dalam pengembangan komponen teknologi. Kapasitas masyarakat di semua tingkatan perlu dikembangkan untuk meningkatkan kemampuan respon kelembagaan di tingkat lokal. Untuk memahami system manajemen bencana dan untuk meningkatkan pasrtisipasi semua pihak, ketersediaan dana yang memadai, pengembangan kapasitas yang cukup merupakan hal yang sangat penting. Hanya proses pembelajaran bersama yang bisa menciptakan suatu strategi yang benar-benar dibutuhkan masyarakat dalam menghadapi bencana. Hasil dan pengalaman dari proses pembelajaran perlu disusun secara sistematis dan didokumentasi dengan baik. Kata Kunci: manajemen bencana, kesiapsiagaan